2012
DOI: 10.1128/jb.00880-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Metabolically Versatile Halophilic Archaeon Haloferax mediterranei, a Poly(3-Hydroxybutyrate- co -3-Hydroxyvalerate) Producer

Abstract: Haloferax mediterranei , an extremely halophilic archaeon, has shown promise for production of poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) from unrelated cheap carbon sources. Here we report the complete genome (3,904,707 bp) of H. mediterranei CGMCC 1.2087, consisting of one chromosome and three megaplasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 20 publications
(12 reference statements)
1
73
1
1
Order By: Relevance
“…mediteranneimediated PHA production has been further optimized by researchers all around the world. Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…mediteranneimediated PHA production has been further optimized by researchers all around the world. Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of published studies evidence the high stability of this organism during long-term continuous cultivation and the convenient recovery of accumulated PHA-granules without the need of organic extraction solvents 33 . In addition, similar to Cupriavidus necator, the best investigated PHA producer 34 , the entire genome sequence of H. mediterranei is deciphered and reported 35 .…”
Section: Pha and Eps From H Mediterraneimentioning
confidence: 99%
“…Currently, progress have been made in understanding the genomes of other species such as Hfx. mediterranei ATCC33500 (Han et al, 2012), Hfx. gibbonsii strain ARA 6 (Pinto, D'Alincourt Carvalho-Assef, Vieira, Clementino & Albano, 2015) or Hfx.…”
Section: Introductionmentioning
confidence: 99%